HISTORICAL OUTLOOK OF CHOLA ENDOWMENTS IN VAZHUVUR VEERATTESWARAR TEMPLE INSCRIPTIONS - MR. G. PRADEEP , DR. V. RAJU (ON DEPUTATION) (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Veerateeswarar Temple, also referred to as the Vazhuvur Veerateeswarar Temple, is a Saiva religious establishment located at Vazhuvur in the contemporary Mayiladuthurai district of Tamil Nadu. The temple is dedicated to Shiva, venerated in the form of Veerateswarar, with the accompanying goddess worshipped as Bala Gujambigai. The site forms part of the early Saiva sacred landscape and reflects the continuity of devotional practice across centuries. The village of Vazhuvur is cited in the seventh-century Tevaram, the foundational Tamil Saiva canonical corpus attributed to the Nayanar poet-saints. While the temple itself is not the subject of an exclusive hymn, its recognition as a Vaippu Sthalam places it among the 276 shrines acknowledged within the Tevaram tradition. This literary reference attests to the antiquity of the site and its embeddedness within early devotional networks. The temple’s historical identity is thus shaped by its textual presence, ritual significance, and enduring association with Tamil Saiva religious culture.